THE LEGAL POSITION OF THE PEACE DEED DISPUTE RESOLUTION IN OUT OF COURT - A Rahim (Journal Indonesia Law and Policy Review, 2020)
This study aims to determine the legal strength of peace deeds outside the court; peace deeds accommodate the interests of the parties and the legal position of peace deeds made outside the court. This research is a normative legal research type. The approach used is the statute approach. All research materials were analyzed using qualitative techniques. The results of this study conclude that the settlement of disputes outside the court will have permanent and binding legal force after the agreement is stated in the form of a peace deed made by a notary and is an authentic deed, namely an act that has perfect legal force. This means that if it turns out that one of the parties denies/defaults, the other party can ask for what has been agreed. Then the peace deed made by the notary has executorial legal force with a decree issued by the head of the District Court containing a request for execution so that the peace deed can be implemented.